TRIDENT - Styrbjörn, Käll (SciLifeLab Serve, 2026)
Predicting chemical EC50 and EC10 ecotoxiticy values towards fish, aquatic invertebrate, and algae for a diverse set of effects using AI. Publication in Science Advances available through DOI: https://doi.org/10.1126/sciadv.adk6669
Keywords: Artificial Intelligence; Cheminformatics; ecotoxicity